Design provision assessment for localized-loading resistance of welded stainless steel I-beams with web openings - Yue Jiang; Lingzhi Li; Lin Zhu; Wenling Xu; Youtian Wang; Boshan Chen; Yaohui Chi; Gaoqiao Wu (Case Studies in Construction Materials)
To optimize space and maintain structural integrity, web openings are often introduced to accommodate building services, limiting their applications. Also, such stainless-steel members serving as I-beams are frequently susceptible to experiencing the localized loading (patch loading) induced by moving load. However, there is a lack of design provisions for the localized-loading resistance prediction of such stainless-steel I-beams with web openings under localized loading. Building on previous experimental work by the authors, this work addresses this gap by performing a comprehensive numerical analysis aimed at developing new design provisions for the localized-loading resistance of such I-beams. The novelty of this work lies in the development of new semi-empirical design equations that incorporate key geometric parameters influencing the strength of perforated stainless steel members. Two commonly used stainless steel (austenitic and duplex) were examined in this work. An advanced numerical model was developed, and the validation process involved a detailed comparison between the numerical results and corresponding experimental data. Following this validation, the same FE modelling approach was employed to perform an extensive parametric study. A total of 2128 numerical findings were reported, evaluating the effects of localized-loading width ratios, web aspect ratios, web slenderness, hole size ratios and initial geometrical deformations. The findings from the parametric analysis were further used to assess the accuracy of the existing design provisions. The comparison highlighted that the existing provisions could not accurately predict the localized-loading resistance of such I-beams. To address this limitation, new simplified design provisions were proposed, and the modified coefficients were applied to the existing design provisions. The comparison findings demonstrated that the new provisions proposed in this work could provide accurate and reliable predictions, offering a significant improvement over the existing design provision.